Epidemiology of amyotrophic lateral sclerosis in the north east Tuscany in the 2018–2021 period - Sabrina Mata; Matteo Bussotti; Monica Del Mastio; Alessandro Barilaro; Patrizia Piersanti; Maria Lombardi; Massimo Cincotta; Sara Torricelli; Deborah Leccese; Martina Sperti; Gabriele Rosario Rodolico; Benedetta Nacmias; et al. (eNeurologicalSci, 2023)
Background: The incidence of Amyotrophic Lateral Sclerosis (ALS) varies among different geographical areas and seems to increase over time. This study aimed to examine the epidemiologic data of ALS in the north-east Tuscany and compare the results with those of similar surveys. Methods: Data from ALS cases diagnosed in Florence and Prato Hospitals were prospectively collected from 1st June 2018 to 31st May 2021. Results: The age- and sex-adjusted incidence rate of ALS in cases per 100,000 population was 2.71 (M/F ratio: 1.21), significantly higher as compared to that reported in the 1967–1976 decade in the same geographical area (0.714). The age- and sex-adjusted incidence rate among resident strangers was similar to that of the general population (2.69). A slightly higher incidence rate (4.36) was observed in the north-east area of Florence province, which includes the Mugello valley. The mean prevalence was of 7.17/100,00. The mean age at diagnosis was 69.7 years, with a peak between 70 and 79 years among men and a smoother age curve among women. Conclusions: ALS epidemiological features in north-east Tuscany are in line with other Italian and European Centers. The dramatic increase of the local disease burden over the last decades probably reflects better ascertainment methods and health system.